Screening of Preliminary Phytochemicals and GC-MS Analysis of Chloroform Extract of Chaetomorpha media (C.Ag.) Kuetzing - P, Anusathya Priya; Paul J, John Peter; C, Iniya Udhaya; E, Fredrick Raja; G, Ponnudurai; M, Muthu Sheeba (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The present study was carried out to analyse the chloroform extract of marine green macro alga Chaetomorpha media (C.Ag.) Kuetzing, belonging to the family Chlorophyceae. Design: The plant materials were collected from Manapad, located in Thoothukudi district, Tamil Nadu, India. The preliminary phytochemical analysis was carried out by Harborne method and followed by the characterization of biochemicals were predicted using GC-MS analysis. Intervention: Among the various solvent extracts, chloroform extract was intervened in this study Main outcome measure: The main measurement results in this study were to determine the presence of various phytochemicals in the chloroform extract of Chaetomorpha media (C.Ag.) Kuetzing Results: In the preliminary phytochemical analysis of the chloroform extract of Chaetomorpha media (C.Ag.) Kuetzing, seventeen different types of secondary metabolites such as alkaloids, anthocyanin, anthraquinone, catechin, cardiac glycosides, coumarins, flavonoids, glycosides, phenolic groups, phlobatannins, phytosteroids, quinones, saponins, tannins, terpenoids, emodins and diterpenes were present in the chloroform extract. GC-MS spectrum of chloroform extract of Chaetomorpha media (C.Ag.) Kuetzing revealed 18 different major peaks which indicated the presence of eighteen compounds. The prevailing compounds in chloroform extract were 6-Methyloctahydro coumarin, Cyclododecane methanol, 2,3,4-Trimethoxyphenyl acetonitrile, Silicic acid, diethyl bis(trimethylsilyl) ester, Propanamide, 3-bromo-N-(4-bromo-2-chlorophenyl), 2-Ethylacridine, Bis(2-ethylhexyl) phthalate, Silane, trimethyl [5-methyl-2-(1-methylethyl)phenoxy], 1H-Indole, 1-methyl-2-phenyl, Benzo[h]quinoline, 2,4-dimethyl, Indole-2-one, 2,3-dihydro-N-hydroxy-4-methoxy-3,3-dimethyl, Tris(tertbutyl dimethylsilyloxy) arsane, [1,2,4]-Triazolo[4,3-a] [1,3,5]-triazine 5,7-diacetylamino-3-methyl, Cyclotrisiloxane, hexamethyl, Benzo[h]quinoline, 2,4-dimethyl, N,N-Dimethyl-4-nitroso-3-(trimethylsilyl) aniline, 2-Methyl-7-phenylindole, 1,1,1,3,5,5,5-Heptamethyltrisiloxane. Conclusion: The chloroform extract of Chaetomorpha media (C.Ag.) Kuetzing showed the presence of various phytochemicals which can be used as medicine to cure various diseases.